Implementasi Strategi Disperindagkop UKM Provinsi Kalimantan Timur dalam Mengoptimalkan Digitalisasi UMKM Kota Samarinda di Era Pandemi Covid-19 - Sarai, Melsy Vanesa; Apriani, Fajar (Jurnal Paradigma, 2026)
The aim of this research is to determine the implementation of strategies for optimizing digitalization in MSMEs in Samarinda City by the East Kalimantan Province UKM Disperindagkop UKM and identify inhibiting factors in the implementation of the East Kalimantan Province UKM Disperindagkop SME strategy. The research approach used is descriptive qualitative with interactive model analysis data analysis techniques. The research results show that the implementation of the strategy by the East Kalimantan Province Disperindagkop UKM has run optimally. Digitalization is a step for the East Kalimantan Province Disperindagkop UKM in empowering MSME players in the era of the Covid-19 Pandemic. However, in its implementation there were several obstacles found in the implementation process, namely MSME players who experienced problems with the unstable internet network in certain places, there were still MSME players who chose to sell conventionally, and there were still MSME players who did not understand how to use digital technology.